Automated Data Capture Technologies: RFID - Potdar, Vidyasagar; Wu, Chen; Chang, Elizabeth (Information Science Reference, 2007)
In this chapter we provide an introduction to RFID technology. We discuss the main components of the RFID technology, which includes RFID transponders, RFID readers, RFID middleware, and RFID labels. A detailed classification and explanation for each of these components is provided, followed by the benefits and applications that can be achieved by adopting this technology. After discussing all possibleapplications, we describe the business benefits and how stakeholders can benefit. This is followed by a detailed outline of the adoption challenges, where we discuss issues like the security, privacy, cost, scalability, resilience, and deployment and some existing solutions. Once the issues are discussed, we divert our attention to some successful RFID deployment case studies to describe the adoption of RFID technology that has already begun and how many big organizations across the world are showing interest in this technology. Since this chapter takes into consideration a variety of audiences like researchers, business executives, business consultants, hobbyists, and general readers, we tried to cover material relevant to each target audience. For business executives and consultants interested in knowing who can offer complete RFID solutions, we allocated a dedicated section for RFID vendors where we provide a comprehensive list of RFID vendors across the globe. For researchers, we listed some open issues in the section of adoption challenges. For advanced users, in-depth technical details are provided in the section where we discuss security and privacy enhancing protocols.